1985
DOI: 10.1007/bf01655194
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous multiple early gastric carcinoma: A study of 178 cases

Abstract: Over the past 3 decades, ending in 1979, resection has been performed in 7,220 patients with gastric carcinoma. Synchronous multiple gastric carcinoma, according to the diagnostic criteria of Moertel, was found in 468, of which 178 (38%) were "early." There were 135 double, 33 triple, and 10 quadruple early earcinomas. Fewer than one-third of the smaller tumors were diagnosed preoperatively, and 61.5% of the smaller lesions were less than 10 mm in diameter. In 53% of the patients, the smaller lesions were in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 5 publications
4
14
0
Order By: Relevance
“…The incidence of synchronous multiple cancer of the stomach has increased recently, and it now constitutes several per cent of all cancers (Moertel et al, 1957;Noguchi et al, 1985). In our study, multiple gastric cancers were found in 7.69% of the elderly and this figure is significantly higher than in the middle-aged group.…”
Section: Symptom Manifestationsupporting
confidence: 51%
“…The incidence of synchronous multiple cancer of the stomach has increased recently, and it now constitutes several per cent of all cancers (Moertel et al, 1957;Noguchi et al, 1985). In our study, multiple gastric cancers were found in 7.69% of the elderly and this figure is significantly higher than in the middle-aged group.…”
Section: Symptom Manifestationsupporting
confidence: 51%
“…As these incidences have increased, the clinicopathological features of EGCs have been gradually elucidated by various authors (Mori et al, 1985;Ohta et al, 1987;Moreaux et al, 1993). The accumulation of patients with EGCs has allowed the investigation of atypical EGCs (Noguchi et al, 1985;Ichiyoshi et al, 1990; Kitamura et al, 1996a); early gastric cancers mimicking advanced gastric cancers (EGC mimicking AGC) is one such variant.…”
mentioning
confidence: 99%
“…This figure, which is very small, is intermediate between a prevalence of 2 and 8% report ed in literature [6][7][8][9][10], and it is a much lower rate than the 22% reported in advanced cancer or in the rare cases of cancer associated with pernicious anemia or multiple gastric polyposis [11,12], The most important point however is that multiple foci are always strictly contiguous to the main lesions and many of them are early gastric cancers.…”
Section: The Problem Of Multicentricitymentioning
confidence: 82%